Taco Bell : the breakfast opportunity - Calkins, Tim (SAGE knowledge. Cases., 2016)
In 2013, Taco Bell was looking for ways to grow. One of the opportunities the company was considering was adding a line of breakfast foods, something the brand had tried - unsuccessfully - before. There were clear reasons to proceed with the launch, as breakfast offered a completely new meal occasion with tremendous potential. However, there were also notable concerns when it came to operational issues and consumer behavior. This case gives students an opportunity to debate growth and new product opportunities.